2010
DOI: 10.1371/journal.pone.0010974
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Enhance Stem-Like Properties and Conditional Malignancy in Gliomas

Abstract: BackgroundSmall populations of highly tumorigenic stem-like cells (cancer stem cells; CSCs) can exist within, and uniquely regenerate cancers including malignant brain tumors (gliomas). Many aspects of glioma CSCs (GSCs), however, have been characterized in non-physiological settings.MethodsWe found gene expression similarity superiorly defined glioma “stemness”, and revealed that GSC similarity increased with lower tumor grade. Using this method, we examined stemness in human grade IV gliomas (GBM) before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…These cells are a specific small population that can initiate tumor growth and sustain self-renewal. Previous studies demonstrated that CSCs could resist traditional therapies and were associated with tumor recurrence (10,11,28). CSC-enriched population isolated from colorectal cancer cells may provide new opportunities for targeted identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells are a specific small population that can initiate tumor growth and sustain self-renewal. Previous studies demonstrated that CSCs could resist traditional therapies and were associated with tumor recurrence (10,11,28). CSC-enriched population isolated from colorectal cancer cells may provide new opportunities for targeted identification.…”
Section: Discussionmentioning
confidence: 99%
“…These cells had been characterized by pluripotency, self-renewal as well as tumorigenicity (7)(8)(9). CSCs were resistant to traditional therapies, leading to tumor recurrence and unpleasant prognosis for cancer patients (10,11). Conventional treatments mainly targeted the tumor cells, but not the CSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus an improvement in this strategy is urgently needed. A possible explanation for these limited clinical results may lie in the failure to target CICs, a hypothesis corroborated by the evidence that an increase in "stemness" profile was obtained in postvaccinated glioblastoma patients and following antitumor T cell activity (8,9). We have previously characterized the immune profile of CICs isolated from glioblastoma multiforme (GBM) tissues and found low immunogenicity (10).…”
mentioning
confidence: 99%
“…In contrast to immune surveillance, tumor immunoediting can select clones that can evade the constraints of immune recognition and/or responses [51]. Illustrating this point, Irvin et al showed that gliomas exposed in vivo to anti-tumor cytotoxic T-lymphocytes activity evolved in a stereotypical way to upregulate highly similar sets of genes in both humans and mice, with the latter acquiring specific resistance to T-cell activity [52]. This observation suggests that immunoediting may represent a prototypical constraint within the tumor microenvironment capable of promoting relatively homogeneous GBM cells.…”
Section: Host Environment Immunity Selection Pressure and Glioma Treamentioning
confidence: 99%